Uji Cemaran Mikroba pada Jajanan Pedagang Kaki Lima Sekolah Dasar di Kecamatan Tarakan Tengah Menggunakan Metode Angka Lempeng Total - Nurfadilah, Nurfadilah; Rukaya, Benazir Evita; Syuhada, Syuhada (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to evaluate the level of microbial contamination in street food sold and to conduct direct observations on environmental sanitation and hygiene practices carried out by street vendors in elementary school environments in Kecamatan Tarakan Tengah. The microbial contamination levels in 15 research samples, consisting of 9 types of food and 6 types of beverages, were randomly obtained from five different sub-districts and measured using the Total Plate Count (TPC) method. During the sampling process, observations and documentation of activities and conditions around the sales locations were conducted. The results of this study indicate that (1) all samples had TPC values far exceeding the limits set by BPOM, with the highest contamination found in pentol ayam goreng (8.69 Ã— 10Â¹â° CFU/g) and es nutrijel stroberi (4.79 Ã— 10Â¹â° CFU/ml); (2) The main factors contributing to the high microbial contamination, based on direct observations during sampling, include poor sanitation practices, exposure to an open environment, and the use of unhygienic equipment. Therefore, it can be concluded that street food sold in the vicinity of elementary schools in Kecamatan Tarakan Tengah presents a significant health risk to students due to the high level of microbial contamination.